The Influence of Communication, Work Motivation and Career Development on Elementary School Teacher’s Job Performance in Medan, Indonesia - Sianturi, Kepler; Tampubolon, Manner (International Journal of Business, Economics and Management, 2017)
Work performance requires the integration of ability, efforts and the opportunity gained. This means that work performance is the result of work for a specified period of time and it accentuates more on the result of work completed for a specified period of time. One of the duties personnel department held responsible for in improving teacher job performance is through providing communication, implementing teacher career development program and motivating teachers so as to create work performance. This study sought to determine the influence of communication, career development and work motivation on work performance of elementary school teachers in Medan, Indonesia. The research was conducted on elementary school teachers in Medan. The research is descriptive quantitative research in nature. Upon analyzing the data, it was discovered that there is a positive and significant influence between the variables of communication (X1), work motivation (X2) and career development (X3) collectively on the dependent variable of work achievement (Y) of elementary school teacher in Medan namely 55,998 and the results of adjusted coefficient of determination (R Square) discovered that the variables of communication (X1), work motivation (X2) and career development (X3) collectively influence the dependent variable of work achievement (Y) amounting to 83,9% which means that R Square = 0,70 is strongly related. Thus, it can be concluded that 70,4% of factors influencing work performance stem from communication, work motivation and career development, whereas the remaining 69.2% is influenced by other factors.